Controlled Synthesis of Different Morphologies of Cu–MgO and Their Application as Catalysts in Synthesis of 1, 2, 3‐Triazoles Following Different Pathways. Issue 24 (28th August 2017) - Roy, Biplab; Panda, Asit B.; Chattopadhyay, Asoke P.
Abstract: Different morphologies of self‐assembled Cu–MgO nanocrystalline materials are prepared following single step hydrothermal route as well as wet impregnation method from pre‐synthesized MgO. These methodologies are simple and robust. Catalytic performance of MgO based materials is highly controlled by their morphology, crystallinity and particle size etc. The synthesized materials are well characterized by conventional instrumental techniques. Usually flakes formed which self‐assembled into different structures like marigold flower, house‐of‐cards, snowflakes and random flakes in several micron sizes. Porosity is observed for such arrangement. Flakes are porous, formed by large number of nanoparticles as building blocks with numerous edges, corners, step edges and step corners. The efficacy of these catalysts is studied in synthesis of 1, 2, 3‐triazole derivatives ('click' reaction) following various methodologies in environmentally benign, economically cheap solvent, water. The methodologies of convention 'click' reaction, which may be superior over our catalysts, were also examined in detail. The catalysts are easily separable and show recyclability with no significant loss in catalytic activity in subsequent cycles. Abstract : Different morphologies of nano‐stuctured Cu–MgO have been synthesized and well characterized. The developed catalysts are investigated to find their efficiency in 'Click' reaction to synthesize 1, 2, 3‐triazoles in water as solvent. Reactions parameters have been optimized to give the highest yield of the desired product. The catalyst was found to be recyclable.